Extruded complete feed for finishing cattle - Strabler, R.; Crisler, A.J.; Depenbusch, Brandon E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Steam flaking is the predominant means of processing grains in large commercial feedlots. Compared with dry rolling, steam flaking improves total tract digestibility and feed efficiency by 8 to 15%. In steam-flaked corn diets, alfalfa hay often is used as a source of roughage. A survey of industry consultants showed that the range of roughage levels used is between 4.5 and 13.5%. Roughages are commonly the highest-cost ingredient per unit of energy and are highly prone to shrink. Low roughage levels are desirable, but a modest level must be maintained to ensure rumen health. Cattle, like other species, can be selective in their eating. We proposed that we could achieve a greater level of grain processing with an extruded processed diet than with steam flaking. In addition, a complete extruded diet would ensure that all cattle received the desired ratio of concentrate and roughage.
Keywords: Beef; Cattle; steam-flaked corn diets